Mortar Improvement Using Nopal Additive - Hernández-Zaragoza, J. B.; Coronado-Márquez, A.; López-Lara, T.; Horta-Rangel, J. (Journal of the Professional Association for Cactus Development, 2008)
Nopal has been used in many applications of building construction in Mexico, since remote times. Now, previous knowledge is being used to find new applications in hydraulic cementitious materials, such as Portland cement used in mortar fabrication. Results of the investigation demonstrate that mortar made with nopal as an additive had a greater compressive strength than mortars made without the additive. The time of setting was improved enormously, that means that the nopal acts as a retardant in mortar manufacture.